Exacerbation of glycoprotein VI-dependent platelet responses in a rhesus monkey model of type 1 diabetes - Arthur, J.; Shen, Y.; Chen, Younan; Qiao, J.; Ni, R.; Lu, Y.; Andrews, R.; Gardiner, E.; Cheng, J. (2013)
Thrombosis is a life-threatening complication of diabetes. Platelet reactivity is crucial to thrombus formation, particularly in arterial vessels and in thrombotic complications causing myocardial infarction or ischaemic stroke, but diabetic patients often respond poorly to current antiplatelet medication. In this study, we used a nonhuman primate model of Type 1 diabetes to measure early downstream signalling events following engagement of the major platelet collagen receptor, glycoprotein (GP)VI. Diabetic monkeys were given enough insulin to maintain their blood glucose levels either at 8 mM (well-controlled diabetes) or 15 mM (poorly controlled diabetes). Flow cytometric analysis was used to measure platelet reactive oxygen species (ROS) generation, calcium mobilisation, receptor surface expression, and immature platelet fraction. We observed exacerbated intracellular ROS and calcium flux associated with engagement of GPVI in monkeys with poorly controlled diabetes. GPVI surface levels did not differ between healthy monkeys or the two diabetic groups. Treatment of platelets with the specific Syk inhibitor BAY61-3606 inhibited GPVI-dependent ROS and, importantly, reduced ROS generation in the poorly controlled diabetes group to that observed in healthy monkeys. These data indicate that glycaemic control is important in reducing GPVI-dependent platelet hyperreactivity and point to a potential antithrombotic therapeutic benefit of Syk inhibition in hyperglycaemic diabetes. © 2013 J. F. Arthur et al.